The Study on Siddha Herbal Formulation Keezhanelli Chooranam for the Treatment of Type 2 Diabetic (Madhumegam): A Review - Soruban, T.; Sathiyaseelan, V. (International Journal of Research in Academic World, 2026)
Diabetes Mellitus (DM) is a common metabolic disorder characterized by high blood glucose levels and symptoms such as polyuria, polydipsia, and polyphagia. Type 2 Diabetes Mellitus (T2DM) is the most prevalent form worldwide and is associated with serious complications including cardiovascular disease, neuropathy, nephropathy, and retinopathy. In Siddha medicine, T2DM can be correlated with Madhumegam. Keezhanelli Chooranam (KNC), prepared from Phyllanthus amarus, is traditionally used in Siddha practice for the management of Madhumegam. This review aims to collect classical Siddha literature evidence and scientific research findings related to KNC, especially its antidiabetic property. Literature from authentic Siddha texts, pharmacopoeias, research articles, and electronic databases were reviewed. Phytochemical studies show that Phyllanthus amarus contains lignans, flavonoids, tannins, alkaloids, and triterpenes, which possess antioxidant, anti-inflammatory, antidiabetic, and anticancer properties. Animal studies suggest significant antidiabetic effects, although human studies show mixed results. Overall, Keezhanelli Chooranam has promising therapeutic potential, but more well-designed clinical trials are required to confirm its safety and effectiveness in humans.
Keywords: Diabetes mellitus; Keezhanelli chooranam; Madhumegam; Phyllanthus amarus and Siddha medicine